Body in the forefront, again? Distance learning drawbacks and implications for policy - Jacomuzzi, Alessandra Cecilia; Milani Marin, Laura Emma (Frontiers in Education, 2024)
The Covid-19 pandemic launched a challenge to the education system and required schools to make organisational changes. Essential to this process are support teachers, who play a key role as agents of change. Despite this, their perspectives, desires and needs have since been neglected, despite their centrality in contemporary Italy. Accordingly, the specific aim of this study revolves around support teachers' experiences with digital technologies (i.e. learning applications, telecommunication media and interactive devices) within a pandemic context; technologies used to maintain the educational bond with students with disabilities. Attuned to an interpretative paradigm, this qualitative research has an ethnographic design, which was implemented in a secondary school in a Northern Italian city. We discuss the three main drawbacks found in fieldwork: i) the prevailing change in bureaucratic management; ii) the pervading mind-body binarism in teaching; iii) a long-term vision for inclusion being subject to a passive logic of adaptation. Lastly, we reflect on some emerging implications. The first points to a necessary move from a rationalistic school management to an alternative model focused more on guaranteeing social justice among educational stakeholders. The second is that the introduction of a new technology should be aimed at engaging actors whose work has been invisible until now in a school setting, so as to empower them as key agents for change. The third suggests that a teacher researcher figure is needed; a figure with holistic skills in addition to those of a technical nature delivered by institutional training programmes.